Polishability and wear resistance of splint material for oral appliances produced with conventional, subtractive, and additive manufacturing. (November 2017) - Huettig, Fabian; Kustermann, Achim; Kuscu, Ebru; Geis-Gerstorfer, Jürgen; Spintzyk, Sebastian
Abstract: Occlusal splints to treat bruxism are commonly made from polymethylmethacrylate (PMMA) in a manual workflow (powder-liquid technique). Today digitalization allows a machine-based manufacturing in subtractive (milling) and additive (printing) means using industrial-made PMMA or comparable resins. An in-vitro study should assess the surface finish and screen the wear resistance of conventional and industrial materials. Therefore, a total of 30 specimens made from conventionally PMMA (group C; powder-liquid, Palapress), polycarbonate ingots (group S; innoBlanc splint plus), and light-curing resin (group A; VarseoWax splint) were polished to examine the surface roughness (Ra) by profilometry and further analyzed by SEM. The specimens were loaded with a steatite ball moving 5000 times along 1 cm with 5 N of surface pressure under constant wetting (artificial saliva). The total height of profile (Pt) was calculated by further profilometry of the specimens. All specimen showed initially comparable Ra values ranging between 0.06 and 0.05 µm (SD = 0.01) after polishing. SEM investigations revealed no visual cues for scratches or irregularities in any group. After abrasion test, the comparison of the wear depths, revealed mean Pt values of 111.4 µm (SD = 18.5) in C, 85.7 µm (SD = 21.5) in S, and 99.1 µm (SD = 21.5) in A, whereas the mean of S was statistically different from C (p = 0.025). No signs of abrasion were found on the steatite balls. All materials showed comparable polished surfaces and a similar scale of wear. It remains questionable if the detected statistical differences are of clinical relevance, but indicates the need for tests of novel materials, especially in additive manufacturing.